The Principal’s Strategy in Improving the Quality of Education - Wirduna, Wirduna; Arafat, Yasir; Destiniar, Destiniar (Journal of Social Work and Science Education, 2022)
This study aims to investigate the strategy for the leadership of the school principal in improving the quality of teachers at SD Negeri Bumi Arum. This study belongs to qualitative. The results showed that the strategy for the leadership of the school principal in improving the quality of teachers was well implemented, by direct coaching, monthly meetings, teacher working group, provide motivation, give awards to teachers, and further study.